Multi-objective sizing optimization of stand-alone photovoltaic-retired electric vehicle battery-diesel generator system using modified honey badger algorithm. - Kamarzaman, Nur Atharah (2025)
Stand-alone photovoltaic (SAPV) systems offer sustainable and reliable electricity solutions for remote areas. However, achieving a technically and economically optimized system remains challenging without accurate system sizing due to the exclusion of detailed component dimensioning and accurate model selection in existing optimization methods. In addition, many existing meta-heuristic algorithms are prone to convergence issues caused by an imbalance in their exploration and exploitation parameter. Moreover, single sizing objective, which optimize either technical reliability through Loss of Power Supply Probability (LPSP) or economic performance through Levelized Cost of Energy (LCOE), fail to capture the trade-offs in hybrid energy systems. Furthermore, commonly used energy storage technologies such as lead-acid and lithium-ion batteries are hindered by reliability and cost concerns. To address these limitations, this thesis presents "Multi-Objective Sizing Optimization of Stand-Alone Photovoltaic-Retired Electric Vehicle Battery-Hydrogen-Diesel Generator System using Modified Honey Badger Algorithm".